Annual reports in computational chemistry. - Wheeler, Ralph A. (Elsevier, 2013)
Annual Reports in Computational Chemistry provides timely and critical reviews of important topics in computational chemistry as applied to all chemical disciplines. Topics covered include quantum chemistry, molecular mechanics, force fields, chemical education, and applications in academic and industrial settings. Focusing on the most recent literature and advances in the field, each article covers a specific topic of importance to computational chemists. Quantum chemistryMolecular mechanicsForce fieldsChemical education and applications in academic and industrial settings.